“Enhancing Emotional Expression in Children through National Games in Art Lessons” - Xidoyeva Mahliyo Bozor qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the use of national games as a pedagogical tool to enhance emotional expression in children during art lessons. It highlights how observing and depicting traditional games can improve creativity, visual literacy, compositional skills, and cultural understanding. Practical strategies for integrating game-based activities into art education are also discussed.